Uncommon bronchopulmonary tumors (excluding bronchopulmonary carcinoma) - Carriquiry, Guillermo; Carusso, Enrique; Fernández, Isabel; Maedo, Noemí; Nin Vivó, Jorge; Martínez Apesteguía, José Luis; Bordes, Daniel (Cirugía del Uruguay, 1997)
Bronchopulmonary carcinoma (PBC) is the most common tumor of the lung.